Biological processes driving soil carbon stabilization and multifuncionality in tropical integrated agricultural systems - Vanolli, Beatriz da Silva (2025)
Soil health is fundamental to aligning agricultural productivity with climate resilience and ecological sustainability. This thesis investigates how soil biological activity, expressed through structural and functional indicators, regulates aggregation, carbon stabilization, and ecosystem functioning in tropical integrated agricultural systems (IAS). Along a clay gradient in Brazil, we demonstrate that biogenic aggregation enhances soil organic carbon (SOC) retention in sandy soils, whereas in clay-rich environments, SOC stabilization is primarily governed by organo-mineral associations. Biogenic aggregates, formed through the interaction between roots and soil organisms, act as structural and biochemical microsites for organic matter transformation and stabilization, though they exhibit short-term trade-offs between carbon input and mineral protection. In degraded sandy soils, crop-livestock integration (CLI) systems improved chemical, physical, and biological indicators of soil health, although the magnitude of these benefits varied with management and depth. Multifunctionality analyses revealed that IAS enhance biologically mediated nutrient cycling but do not always improve structural and carbon-related functions, underscoring the need for management strategies that reinforce belowground biological processes. Finally, a field-ready visual guide for assessing biogenic soil structures is presented as a practical tool for monitoring soil health in tropical agroecosystems. Collectively, these findings demonstrate that carbon fractions and soil resilience in IAS are governed by the synergistic interactions among biological activity, soil structure, and mineral associations, underscoring the importance of function-oriented, context-specific management strategies for climate-resilient tropical agriculture